Evaluation of the Antibiofilm Efficacy of Ammonium Chloride (NH4Cl) Against Gram-Negative Bacterial Isolates - Alzubaidy, Fatima Hamza; Al-mohammadawy, Zainab H.; Taklef , Najla K. (Medical Science Journal for Advance Research, 2026)
Background: The bacterial Biofilms, which are communities of bacteria shielded by an Extracellular Polymeric Substance (EPS) matrix, contribute to over 65% of clinical infections and exhibit resistance levels up to 1,000 times higher than free-floating (planktonic) bacteria, so lead to increased antimicrobial resistance. Method: The study evaluated the antibiofilm efficacy of Ammonium Chloride (NH4Cl) against 111 Gram-negative bacterial isolates. The bacteria were detected by vitek-2-compact system, then The biofilm was identified by the tissue culture plate method, after that tested the activity of NH4Cl at two concentrations (0.5, 1mg/mL). Result: From 111 Gram-negative bacterial isolates in current study,20 isolate was not growth while 91 was detected as Escherichia coli, Proteus mirabilis, Pseudomonas aeruginosa, Klebsiella pneumoniae and Acinetobacter baumanii at different ratio. Then detect the biofilm production for 91 isolate, 38 have the ability to form biofilm . The Ammonium Chloride established a strong, dose-dependent inhibitory effect on the bacterial biofilm formation. The biofilm creation was reduced to (71.1% and 100% eradication by 0.5, 1 mg/ml ) concentration, respectively. Conclusion: The concentration of 1 mg/mL from Ammonium Chloride efficiently founding as the Minimum Biofilm Inhibitory Concentration (MBIC) for the isolates tested.